Improvement in Sensory Characteristics of Campbell Early Wine by Adding Dual Starters of Saccharomyces cerevisiae and Oenococcus oeni - Yoo, K.S., Chungbuk National University, Cheongju, Republic of Korea; Kim, J.E., Chungbuk National University, Cheongju, Republic of Korea; Seo, E.Y., Chungbuk National University, Cheongju, Republic of Korea; Kim, Y.J., Chungbuk National University, Cheongju, Republic of Korea; Choi, H.Y., Chungbuk National University, Cheongju, Republic of Korea; Yoon, H.S., Chungcheongbuk-do Agricultural Research and Extension Services, Ochang, Republic of Korea; Kim, M.D., Kangwon National University, Chuncheon, Republic of Korea; Han, N.S., Chungbuk National University, Cheongju, Republic of Korea (Journal of microbiology and biotechnology, 2010)
This study was performed to investigate the effects of adding a dual starter on the chemical and sensory characteristics of red wine made of Campbell Early grape. The yeast starter, Saccharomyces cerevisiae, and lactic acid bacteria (LAB) starter, Oenococcus oeni, were used for inoculation in the winemaking process for alcoholic fermentation and malolactic fermentation (MLF), respectively. After 200 days of incubation, the chemical compositions of yeast/LAB-added wine (YL-wine) were compared with those of no-starter-added wine (control) and yeast-added wine (Y-wine). The results show that no significant differences were observed in pH, total sugar, and alcohol content among the wine samples, but the malic acid content in YL-wine was significantly reduced, and various esters and higher alcohols were synthesized. The sensory test revealed that the addition of dual starters resulted in improved overall acceptability in wine. This study emphasizes the importance of O. oeni in addition to yeast in making Campbell Early wine.